“Dos cortes das piaçavas à pesca da garoupa”: contrabandistas, vereadores, juízes – trajetórias e experiências de Professores Públicos Primários na Comarca de Porto Seguro (1834-1875) - Lisboa, Antonio Barbosa (2018)
This study shows the multiple activities of primary teachers in the district of Porto Seguro, Bahia Province, in the XIX century, while traditional experiences that were against the discipline of the magisterium in the XIX century. Through an approach that favors the search and weaving of traces, it deals with the trajectories and experiences of primary public teachers José Martins Sampaio, José Gabriel da Rocha Lei, Vicente Ferreira Ramos and Manoel Auxílio de Figueiredo. Anchored in concepts and interpretative bases of English social history, French social and cultural history and microhistory it reflects the commercial and political experiences of these subjects in relation to the tensions triggered in the progressive institutionalization of the primary magisterium, demarcated, above all, for a time and discipline of work and an economic use of that time. Taking the district of Porto Seguro as a unit of analysis, the experiences were apprehended through the variation of observation´s scale and comparative historical experiences, which were possible from the selection, crossing and documentary criticism, prioritizing the use of official sources of education, civil documents, justice and local administration documents, analyzed through the indicial paradigm and nominative methodology. His trajectories show customary ways of living with the primary teaching and practices that created tension with the legal order